Pursuing early catheter ablation to treat atrial fibrillation in the congestive heart failure population: significance of the AATAC trial results - Phillips, Karen P. (Journal of Thoracic Disease, 2016)
The current 2013 ACCF/ AHA Clinical Guideline for the Management of Heart Failure state that a rhythm-control strategy has not been shown to be superior to a rate-control strategy in patients with heart failure who develop AF (1). Further it states that the main goals of therapy should simply be the prevention of thromboembolism and symptom control (1). The recommendations are based on a randomized control trial which compared a rhythm strategy using predominantly Amiodarone and electrical cardioversion with standard rate control and showed no significant difference in mortality (2). The ‘prevalence’ of atrial fibrillation on 12 lead electrocardiography at 4 years follow-up was 27% in the rhythm control group and ranged between 59 and 70% over follow-up in the rate control arm (2). However catheter ablation has been shown to be remarkably more efficacious at achieving long term sinus rhythm and freedom from AF than antiarrhythmic drug therapy (3) and a randomized control trial to examine outcomes in a heart failure population had been anxiously awaited.